Dual-network fiber-hydrogel membrane for osmotic energy harvesting - Cao, Licheng; Wu, Huiqing (Frontiers in Chemistry, 2024)
Osmotic energy harvesting was a promising way to alleviate energy crisis with reverse electrodialysis (RED) membrane-based technology. Charged hydrogel combined with other materials was an effective strategy to overcome problems, including restricted functional groups and complicated fabrication, but the effect of the respective charges of the two materials combined on the membrane properties has rarely been studied in depth. Herein, a new method was proposed that charged hydrogel was equipped with charged filter paper to form dual network fiber-hydrogel membrane for osmotic energy harvesting, which had excellent ion selectivity (beyond 0.9 under high concentration gradient), high ion transference number and energy conversion efficiency (beyond 32.5% under wide range concentration gradient), good property of osmotic energy conversion (∼4.84 W/m2 under 50-fold KCl and ∼6.75 W/m2 under simulated sea water and river water). Moreover, the power density was attributed to the surface-space charge synergistic effect from large amounts overlapping of electric double layer (EDL), so that the transmembrane ion transport was enhanced. It might be a valid mode to extensively develop the osmotic energy harvesting.